The development of a snow cleaning system for micro-CMM stylus tips - Feng, Xiaobing; Lawes, Simon; Kinnell, Peter K. (2015)
Contamination adhered to the surface of a µCMM stylus tip significantly impairs the dimensional accuracy of the CMM systems, potentially causing dimensional errors that are over ten times larger than the uncertainty of a modern µCMM. To reduce such errors, this study investigates removing the surface contamination on µCMM stylus tips using a high velocity flow of CO2 gas and sublimated particles. This process is known as snow cleaning. Two different types of snow cleaners were evaluated in the study, and a novel multi-nozzle system developed to address the challenges of cleaning occluded features and balancing forces on the stylus. Studies considered cleaning quality, coverage, and force imparted on the stylus tip. Results have shown that a cleaning force close to the rated probing force of the styli can be achieved. Initial results show that the developed cleaning device was able to eliminate the need for stylus rotation and reduce net force, bringing it closer to on-machine cleaning application.